الإسعافات الأولية.. ثقافة ذاتية ترفع من الوعي الصحي في المدارس دراسة حالة (مدارس المرحلة الابتدائية منطقة النواحي الاربعة) (Comprehensive Journal of Science, 2025)
The study aims to identify primary school teachers' awareness of first aid in primary schools in the Al-Nawayah Al-Arba'a region. The study adopted a descriptive-analytical approach, and a questionnaire was used as a research tool. After verifying its validity and reliability, it was applied to a sample of (208) male and female teachers. The study results showed that the average awareness scores of primary school teachers in the Al-Nawayah Al-Arba'a region schools were slightly above average. The results also revealed statistically significant differences between primary school teachers' awareness of first aid in these schools, attributable to gender, academic qualification, and experience, in favor of intermediate diploma qualifications and (11) years of experience or more.